How intersectional constructions of sexuality, culture, and masculinity shape identities and sexual decision-making among men who have sex with men in coastal Kenya. Issue 6 (2nd June 2016) - Midoun, Miriam; Shangani, Sylvia; Mbete, Bibi; Babu, Shadrack; Hackman, Melissa; van der Elst, Elise M.; Sanders, Eduard J.; Smith, Adrian D.; Operario, Don
Abstract: Men who have sex with men are increasingly recognised as one of the most vulnerable HIV risk groups in Kenya. Sex between men is highly stigmatised in Kenya, and efforts to provide sexual health services to men who have sex with men require a deeper understanding of their lived experiences; this includes how such men in Kenya construct their sexual identities and how these constructions affect sexual decision-making. Adult self-identified men who have sex with men ( n = 26) in Malindi, Kenya, participated in individual interviews to examine sociocultural processes influencing sexual identity construction and decision-making. Four key themes were identified: (1) tensions between perceptions of 'homosexuality' versus being 'African', (2) gender-stereotyped beliefs about sexual positioning, (3) socioeconomic status and limitations to personal agency and (4) objectification and commodification of non-normative sexualities. Findings from this analysis emphasise the need to conceive of same-sex sexuality and HIV risk as context-dependent social phenomena. Multiple sociocultural axes were found to converge and shape sexual identity and sexual decision-making among this population. These axes and their interactive effects should be considered in the design of future interventions and other public health programmes for men who have sex with men in this region.